Ultra low loss broadband 1 × 2 optical power splitters with various splitting ratios - Goudarzi, Kiyanoush; Kim, Doyoung; Lee, Haneol; Park, Ikmo; Han, Haewook (Optics Continuum, 2022)
We designed Si-based all-dielectric 1 × 2 TE and TM power splitters with various splitting ratios by combining the use of the inverse design of adjoint and numerical 3D finite-difference time-domain methods. The structure of the designed Si-based power splitters contains two Si waveguide branches on a SiO2 substrate that is compatible with CMOS fabrication technology. The proposed devices exhibit ultra-high transmission efficiency above 98 and 99%, and excess losses below 0.1 and 0.035 dB, for TE and TM splitters, respectively. The merits of these devices include a minor footprint of 2.2 × 2.2 µm2 and a flat-broad operating bandwidth of 200 nm with a center wavelength of λ = 1.55 µm. Also, the other advantage of these optical power splitters is the very short optimization time of 2 h for each device. Because of the aforementioned merits, the optimized devices can be crucial candidates for optical integrated circuits.
Keywords: 3d finite difference time domains; Adjoints; Inverse designs; Low-loss; Optical power splitters; Power splitters; Si-based; Si-waveguide; Splitting ratio; Waveguide branch